Inter-annual variations of macrobenthic communities over three decades in a land-locked coastal lagoon (Santo André, SW Portugal) - Correia, M.J. (2012)
Santo André is an enclosed brackish water coastal lagoon with temporary connections to the sea by a man-made channel. The exchange and mixture of saltwater and freshwater is irregular and the lagoon may show daily and seasonal fluctuations, but also long-term variation. Different benthic communities may be present along the annual cycle according to the magnitude of episodic freshwater and sea water inputs. In the last 30 years the communication with the sea has followed different regimes from year to year and, as a consequence, macrobenthic communities, assessed several times during the period before the opening to the sea, shifted from freshwater to marine affinities. Major differences were found between 1979 and 2010, with a preponderance of species with marine affinity, and the 1980s in which the organisms with freshwater affinity prevailed. Benthic communities are frequently used to assess aquatic environmental condition. Metrics used in the indices currently under discussion to assess ecological status of aquatic ecosystems within the scope of European Water Framework Directive were applied to Santo André data and the applicability of these metrics to assess quality in this coastal land-locked lagoon was discussed